Translation Strategies in Tempo English Magazine - Salma Felia Nisa; Amin Basuki (Lexicon, 2020)
This research aims at identifying and examining the translation strategies applied in Tempo English magazine, the English edition of Tempo magazine. The data were gathered from 10 selected articles of the source magazine, Tempo, and its translated magazine, Tempo English, both of which belonged to the edition of April 30 – May 6, 2018. The analysis and categorization were based on the news translation theory proposed by Bielsa and Bassnett and supported by Joan Cutting’s context theory as well. The result of this research shows that the translators of Tempo English magazine used all of the news translation strategies in translating the Indonesian news articles to English. There were 199 data found in the research with 77 data of the Addition strategy, 68 data of the Elimination, 25 data of the strategy of Summarizing Information, 15 data of the Change in the Order of Paragraphs, and the other 14 data using the Change of Title and Lead. The research analysis concludes that in the strategy of the Change in the Order of Paragraphs, Tempo English magazine tended to apply the change of order at the phrase and sentence level rather than at the paragraph level.